Integrated inductor and preparation method and application thereof
By combining high-crystalline magnetic powder with medium-crystalline magnetic powder, using its unique structure and magnetic properties, the problems of high loss and low inductance value under high frequency conditions are solved, and high inductance value and Low loss effect.
Patent Information
- Application Number
- CN202411663619.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
The existing chip inductor has high loss and low inductance value under high frequency conditions, making it difficult to meet the needs of high inductance and low loss.
The combination of high-crystalline magnetic powder and medium-crystalline magnetic powder has an amorphous phase surrounding nanocrystalline phase structure, and high-crystalline magnetic powder has a high magnetic permeability through optimized grading and Integrated molding process, an integrated inductor with high inductance value and low loss is prepared.
It realizes an inductor with excellent loss characteristics and high magnetic permeability under high frequency conditions, and improves the inductance value and efficiency.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metallic soft magnetic materials and devices, and in particular to an integrated inductor and a preparation method and application thereof. Background Art
[0002] Chip inductors are key components of chip power modules, and are mainly responsible for providing front-end power to various chips (GPU, CPU, ASIC, FPGA) on the motherboard and graphics card, and providing stable power to ensure the normal operation of the chip. Currently, mainstream chip inductors are mainly made of ferrite materials, but with the development trend of miniaturization, low voltage and high current of power modules, ferrite materials are limited by their low saturation flux density and other conditions, and it is difficult to meet subsequent development needs.
[0003] Chip inductors developed based on metal soft magnetic materials have the advantages of low voltage, high current and small size, and are more suitable for application scenarios that require a lot of computing and processing, such as artificial intelligence, autonomous driving, servers, communication power supplies, and laptops. Metal soft magnetic materials include iron powder cores, iron nickel, iron silicon or iron silicon aluminum, all of which have the characteristics of high saturation magnetization intensity, high current resistance, good constant magnetic permeability, high Curie temperature and good heat dissipation. At present, more and more chip inductors use the above-mentioned metal soft magnetic materials and coils to form an integrated and co-fired process, which has the advantages of high current density, low loss and high magnetic permeability below 1MHz. However, as the application frequency becomes higher and higher, the loss and inductance conversion efficiency of metal soft magnetic materials have reached a certain bottleneck and are difficult to improve further.
[0004] Studies have shown that amorphous nanocrystalline soft magnetic materials have better loss characteristics at high frequencies above MHz, and are often used in the integrated inductor preparation process of low-pressure molding + low-temperature baking. However, due to their low magnetic permeability, the inductance value cannot be further increased, thus limiting their use in high-inductance inductors.
[0005] CN112735797A discloses an integrated co-fired inductor and its preparation method and application. The inductor is made of amorphous nanocrystalline, iron-nickel, iron-silicon-aluminum and iron-silicon materials through high-temperature sintering. The inductance of amorphous and nanocrystalline materials is relatively low, and the DC superposition and efficiency do not show obvious advantages compared with metal magnetic powder. The problem of low magnetic permeability of amorphous nanocrystalline soft magnetic materials still exists. At the same time, after high-temperature heat treatment, the characteristics of low loss at high frequency are not reflected.
[0006] CN112435844A discloses an integrated co-fired inductor and its preparation method, wherein iron-based, nickel-based or cobalt-based amorphous nanocrystalline soft magnetic powder is sequentially treated with insulation coating, secondary coating and granulation as magnetic powder, and then molded and heat treated to obtain a magnetic core, and the wire extending out of the magnetic core is bent and tinned to obtain a co-fired inductor. Under light load conditions, the loss of the device is reduced, there is no additional gap between the wire and the magnetic core, and the air gap is evenly distributed in the magnetic core, reducing the vibration noise of eddy current loss. However, although the initial inductance of the co-fired inductor is improved, the improvement effect is limited, and under high frequency conditions, the efficiency is still not high, and the loss at high frequency is not mentioned.
[0007] Therefore, how to develop a high-inductance chip inductor and its preparation process so that it has a high inductance value and good high-frequency loss characteristics has become a problem that needs to be solved urgently. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides an integrated inductor and a preparation method and application thereof. The present invention combines high-crystallization magnetic powder and medium-crystallization magnetic powder as the internal magnetic powder of the integrated inductor. The soft magnetic material prepared from the medium-crystallization magnetic powder having a structure in which an amorphous phase surrounds a nanocrystalline phase has excellent loss characteristics under high-frequency conditions above MHz. At the same time, the high-crystallization magnetic powder has the advantage of high magnetic permeability. After the two are optimized and graded, the integrated inductor can further have excellent loss characteristics under high-frequency conditions while taking into account higher magnetic permeability, that is, it has a higher inductance value at the same time.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides an integrated inductor, wherein the integrated inductor includes medium-crystallization magnetic powder and high-crystallization magnetic powder;
[0011] The medium-crystallinity magnetic powder has a crystallinity of 40%-80%, such as 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, etc.;
[0012] The crystallinity of the high crystallinity magnetic powder is greater than 95%, such as 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5% or 99.9%, etc.;
[0013] The structure of the medium-crystallized magnetic powder is a structure in which an amorphous phase surrounds a nanocrystalline phase.
[0014] In the present invention, the medium-crystallized magnetic powder has a structure in which an amorphous phase surrounds a nanocrystalline phase. The medium-crystallized magnetic powder of this structure has a magnetostriction coefficient close to 0 under high-frequency conditions above MHz, and the coercive force is the lowest, so the loss is lower, and the soft magnetic material has excellent loss characteristics, but the corresponding magnetic permeability is low, resulting in a low inductance value, which limits its use in high-inductance inductors. When the high-crystallized magnetic powder and the medium-crystallized magnetic powder are combined as the internal magnetic powder of an integrated inductor, the advantage of the high-crystallized magnetic powder having a high magnetic permeability can be utilized, so that the integrated inductor can further have a lower loss value under high-frequency conditions, while also taking into account a higher magnetic permeability, that is, it also has a higher inductance value.
[0015] As a preferred technical feature of the present invention, the grain size of the medium-crystallized magnetic powder is 10nm-100nm, for example, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm.
[0016] Preferably, in a two-dimensional plane, the ratio of the number of particles of the high-crystallinity magnetic powder to the number of particles of the medium-crystallinity magnetic powder is (5-30):1, for example, 5:1, 8:1, 10:1, 12:1, 15:1, 18:1, 20:1, 22:1, 25:1, 28:1 or 30:1, etc.
[0017] In the present invention, the two-dimensional plane refers to a plane corresponding to any cross section in the integrated inductor.
[0018] In the present invention, by limiting the ratio of the number of particles of the high-crystallization magnetic powder to the number of particles of the medium-crystallization magnetic powder to (5-30):1, it can be ensured that the integrated inductor has a higher magnetic permeability and a higher inductance value under high-frequency conditions.
[0019] Preferably, the iron content of the medium-crystallinity magnetic powder is 70wt%-95wt%, for example, 70wt%, 75wt%, 80wt%, 85wt%, 90wt% or 95wt%.
[0020] Preferably, the iron content of the high-crystallization magnetic powder is 45wt%-95wt%, for example, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt% or 95wt%, etc.
[0021] In a second aspect, the present invention further provides a method for preparing the integrated inductor according to the first aspect, the method comprising the following steps:
[0022] Mixing low-crystallization magnetic powder, high-crystallization magnetic powder, a coating agent, a binder and a release agent to obtain a mixed powder; integrally forming a coil with the mixed powder, and after annealing, obtaining an integrated inductor;
[0023] The crystallinity of the low crystallinity magnetic powder is less than 30%, such as 29.9%, 28%, 25%, 23%, 20%, 18%, 15%, 12%, 10%, 8%, 5%, 3%, 1% or 0.5%, etc.;
[0024] The integrated inductor includes medium crystallization degree magnetic powder and high crystallization degree magnetic powder inside; the crystallization degree of the medium crystallization degree magnetic powder is 40%-80%; the crystallization degree of the high crystallization degree magnetic powder is greater than 95%; the structure of the medium crystallization degree magnetic powder is an amorphous phase surrounding a nanocrystalline phase structure.
[0025] In the present invention, a mixed powder with high magnetic permeability can be obtained by optimizing the grading of low-crystallization magnetic powder and high-crystallization magnetic powder. After the mixed powder is integrally formed with a coil and annealed, part of the atoms inside the grains of the low-crystallization magnetic powder are rearranged, and the crystals are surrounded to form a nanocrystalline phase structure surrounded by an amorphous phase, thereby improving the crystallinity. Combined with the addition of high-crystallization magnetic powder, an integrated inductor with a high inductance value can be directly prepared, and the preparation process is simple and easy to operate.
[0026] As a preferred technical feature of the present invention, the method of mixing low-crystallization magnetic powder, high-crystallization magnetic powder, coating agent, binder and release agent comprises:
[0027] The low-crystallization magnetic powder, high-crystallization magnetic powder and coating agent are first mixed, and then a binder is added and mixed, granulated, sieved, and then a release agent is added and mixed.
[0028] It should be noted that the present invention does not make any specific requirements or special limitations on the mixing. As long as it is a mixing method commonly used by those skilled in the art, it is applicable to the present invention, for example, it can be manual mixing, mixer mixing or ball mill mixing.
[0029] As a preferred technical feature of the present invention, the iron content of the low-crystallization magnetic powder is 70wt%-95wt%, for example, 70wt%, 72wt%, 75wt%, 78wt%, 80wt%, 82wt%, 85wt%, 88wt%, 90wt%, 92wt% or 95wt%, etc.
[0030] It should be noted that the low-crystallization magnetic powder used in the present invention includes, in addition to iron, silicon, niobium, copper and boron; wherein the silicon content is 0-12wt%, the niobium content is 0-10wt%, the copper content is 0-5wt%, and the boron content is 0-8wt%, and none of them is 0.
[0031] In the present invention, the iron content of the low-crystallization magnetic powder is adjusted to 70wt%-95wt%, and then the heat treatment temperature of the low-crystallization magnetic powder is adjusted, so that the inductor magnetic permeability obtained by the mixed magnetic powder is improved, the loss is reduced, and the inductance value and efficiency are optimized.
[0032] Preferably, the particle size D50 of the low-crystallization magnetic powder is 5 μm-50 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm.
[0033] Preferably, based on the total mass of the low-crystallinity magnetic powder and the high-crystallinity magnetic powder, the content of the low-crystallinity magnetic powder is 10wt%-90wt%, for example, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or 90wt%, etc.
[0034] As a preferred technical feature of the present invention, the iron content of the high-crystallization magnetic powder is 45wt%-95wt%, for example, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt% or 95wt%, etc.
[0035] It should be noted that the high-crystallization magnetic powder used in the present invention includes nickel, silicon, aluminum and chromium in addition to iron; among them, the nickel content is 0-80wt%, the silicon content is 0-15wt%, the aluminum content is 0-10wt%, and the chromium content is 0-5wt%, and none of them is 0.
[0036] Preferably, the particle size D50 of the high crystallinity magnetic powder is 1 μm-10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.
[0037] As a preferred technical feature of the present invention, the coating agent includes any one of kaolin, talc or mica powder, or a combination of at least two of them.
[0038] Preferably, based on the total mass of the low-crystallinity magnetic powder and the high-crystallinity magnetic powder, the added amount of the coating agent is 0.1wt%-3wt%, for example, 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 2wt%, 2.3wt%, 2.5wt%, 2.8wt% or 3wt%, etc.
[0039] It should be noted that the present invention does not make any specific requirements or special limitations on the adhesive. Different types of adhesives have little effect on the performance of the resulting integrated inductor. As long as the type is commonly used by technicians in this field, it is applicable to the present invention, for example, it can be epoxy resin, phenolic resin or silicone resin.
[0040] Preferably, based on the total mass of the low-crystallinity magnetic powder and the high-crystallinity magnetic powder, the added amount of the binder is 0.5wt%-3wt%, for example, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%, etc.
[0041] Preferably, the release agent includes any one of zinc stearate, aluminum stearate or calcium stearate, or a combination of at least two of them.
[0042] Preferably, based on the total mass of the low-crystallization magnetic powder and the high-crystallization magnetic powder, the added amount of the release agent is 0.5wt%-2wt%, for example, 0.5wt%, 1wt%, 1.5wt% or 2wt%.
[0043] It should be noted that the present invention does not impose any specific requirements or special limitations on the coil. As long as the coil material is commonly used by those skilled in the art, it is applicable to the present invention, for example, it can be a copper coil.
[0044] As a preferred technical feature of the present invention, the integral molding pressure is 500MPa-2000MPa, for example, 500MPa, 800MPa, 1000MPa, 1200MPa, 1500MPa, 1800MPa or 2000MPa.
[0045] Preferably, the annealing temperature is 300°C-700°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C.
[0046] In the present invention, according to the iron content of the low-crystalline magnetic powder, the annealing temperature is adjusted at 300°C-700°C, which can ensure that the low-crystalline magnetic powder can undergo a crystallization reaction, so that the crystallinity of the low-crystalline magnetic powder is improved, thereby transforming into a medium-crystalline magnetic powder with an amorphous phase surrounding a nanocrystalline phase structure, thereby having good high-frequency loss characteristics and improving overall performance.
[0047] Preferably, the annealing time is 0.1 h-5 h, for example, 0.1 h, 0.5 h, 1 h, 2 h, 3 h, 4 h or 5 h.
[0048] As a preferred technical feature of the present invention, the preparation method comprises the following steps:
[0049] First, a low-crystallization magnetic powder with an iron content of 70wt%-95wt%, a particle size D50 of 5μm-50μm, and a crystallinity of less than 30%, a high-crystallization magnetic powder with an iron content of 45wt%-95wt%, a particle size D50 of 1μm-10μm, and a crystallinity of more than 95% and a coating agent are mixed, and then a binder is added to mix, granulate, sieve, and then a release agent is added to mix to obtain a mixed powder; a coil and the mixed powder are integrally formed under a pressure of 500MPa-2000MPa, and after annealing at 300℃-700℃ for 0.1h-5h, an integrated inductor is obtained;
[0050] The integrated inductor includes medium crystallinity magnetic powder and high crystallinity magnetic powder; the crystallinity of the medium crystallinity magnetic powder is 40%-80%, and the crystallinity of the high crystallinity magnetic powder is >95%; the structure of the medium crystallinity magnetic powder is an amorphous phase surrounding a nanocrystalline phase structure; based on the total mass of the low crystallinity magnetic powder and the high crystallinity magnetic powder, the content of the low crystallinity magnetic powder is 10wt%-90wt%; based on the total mass of the low crystallinity magnetic powder and the high crystallinity magnetic powder, the added amount of the coating agent is 0.1wt%-3wt%, the added amount of the binder is 0.5wt%-3wt%, and the added amount of the release agent is 0.5wt%-2wt%.
[0051] In a third aspect, the present invention further provides an application of an integrated inductor, wherein the integrated inductor described in the first aspect, or the integrated inductor prepared by the preparation method described in the second aspect, is applied to a magnetic component.
[0052] Compared with the prior art, the present invention has at least the following beneficial effects:
[0053] 1) The integrated inductor of the present invention includes medium-crystallization magnetic powder and high-crystallization magnetic powder, which can enable the integrated inductor to have excellent loss characteristics and high magnetic permeability under high-frequency conditions, that is, to have a high inductance value at the same time.
[0054] 2) The present invention optimizes the grading of low-crystalline magnetic powder and high-crystalline magnetic powder to obtain a mixed powder with high magnetic permeability, and then combines the one-piece molding process and the annealing process to transform the low-crystalline magnetic powder into a medium-crystalline magnetic powder with an amorphous phase surrounding a nanocrystalline phase structure, thereby directly obtaining an integrated inductor with low loss and high inductance value in one step. The preparation process is simple and easy to operate. DETAILED DESCRIPTION
[0055] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0056] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0057] In the specific implementation method of the present invention, the crystallinity of low-crystalline magnetic powder, medium-crystalline magnetic powder and high-crystalline magnetic powder is obtained by X-ray diffractometer (XRD) and transmission electron microscope (TEM) tests; the content of iron and other elements in the low-crystalline magnetic powder and high-crystalline magnetic powder is obtained by inductively coupled plasma (ICP) testing.
[0058] Example 1
[0059] This embodiment provides an integrated inductor, wherein the integrated inductor includes a medium-crystallization magnetic powder with a crystallinity of 55% and a high-crystallization magnetic powder with a crystallinity of 99%; the structure of the medium-crystallization magnetic powder is an amorphous phase surrounding a nanocrystalline phase structure;
[0060] The preparation method comprises the following steps:
[0061] First, a low-crystalline magnetic powder (80wt%) with an iron content of 93wt%, a particle size D50 of 15μm, and a crystallinity of 5%, a high-crystalline magnetic powder (20wt%) with an iron content of 75wt%, a particle size D50 of 2μm, and a crystallinity of 99%, and 1wt% of kaolin (based on the total mass of the low-crystalline magnetic powder and the high-crystalline magnetic powder) are mixed, and then 1.2wt% of a binder (based on the total mass of the low-crystalline magnetic powder and the high-crystalline magnetic powder) is added to mix, granulate, sieve, and then 0.3wt% of zinc stearate is added to mix to obtain a mixed powder; a copper coil and the mixed powder are integrally formed under a pressure of 1800MPa, and after annealing at 540°C for 2h, an integrated inductor is obtained.
[0062] Examples 2-10 and Comparative Examples 1-2 are based on the steps of Example 1 with parameter changes, and the specific changed parameters are shown in Table 1.
[0063] The inductance, no-load loss and efficiency of the integrated inductors prepared in Examples 1-10 and Comparative Examples 1-2 were tested under the following test conditions:
[0064] Inductance test: at 1MHz / 1V, the inductance value is tested when the loading current is 0A, 80A and 120A; no-load loss and efficiency test: 12V to 1V, frequency 1MHz, test no-load loss and efficiency value when the loading current is 10A and 20A; the specific test data are shown in Table 1.
[0065] Table 1
[0066]
[0067]
[0068]
[0069] Note: “ / ” indicates that the raw material was not added.
[0070] The test results show that:
[0071] (1) It can be seen from Examples 1 to 6 that the present invention optimizes the grading of low-crystalline magnetic powder and high-crystalline magnetic powder, and forms a mixture of medium-crystalline magnetic powder and high-crystalline magnetic powder with amorphous surrounding nanocrystalline structure through one-piece molding and annealing process. The prepared one-piece inductor has excellent inductance value, no-load loss and efficiency at high frequency. The initial inductance value is 110nH-124nH, the no-load loss is 0.54W or less, as low as 0.47W, and the efficiency is 90.5% or more under 10A and 20A loads.
[0072] (2) It can be seen from Examples 7 to 8 that the present invention further regulates the iron content in the low-crystallization magnetic powder to 70wt%-95wt%, and then regulates the heat treatment temperature of the low-crystallization magnetic powder, so that the magnetic permeability of the inductor obtained by the mixed magnetic powder is improved, the loss is reduced, and the inductance value and efficiency are optimized.
[0073] (3) It can be seen from Examples 9 and 10 that the present invention can ensure that the low-crystalline magnetic powder fully undergoes a crystallization reaction by further regulating the annealing temperature in the preparation process at 300°C-700°C, thereby improving the crystallinity of the low-crystalline magnetic powder, thereby converting it into a medium-crystalline magnetic powder with an amorphous phase surrounding a nanocrystalline phase structure, thereby having good high-frequency loss characteristics. On the other hand, it can also avoid excessive crystallization, and the medium-crystalline magnetic powder with an amorphous phase surrounding a nanocrystalline phase structure cannot be obtained, and the grain growth will also affect the performance of the inductor.
[0074] (4) It can be seen from Example 1 and Comparative Examples 1 and 2 that when the present invention combines high-crystallization magnetic powder and medium-crystallization magnetic powder as the internal magnetic powder of the integrated inductor, the advantage of high-crystallization magnetic powder having high magnetic permeability can be utilized to further enable the integrated inductor to have both lower loss value and higher inductance value under high-frequency conditions; when only a single magnetic powder is used to prepare the inductor, the inductance value and efficiency under high frequency are significantly reduced, and the no-load loss is significantly increased.
[0075] In summary, the present invention combines high-crystallization magnetic powder and medium-crystallization magnetic powder as the internal magnetic powder of the integrated inductor. The soft magnetic material prepared from the medium-crystallization magnetic powder having a structure in which an amorphous phase surrounds a nanocrystalline phase has excellent loss characteristics under high-frequency conditions above MHz. At the same time, the high-crystallization magnetic powder has the advantage of high magnetic permeability. After the two are optimized and graded, the integrated inductor can further have excellent loss characteristics under high-frequency conditions while taking into account higher magnetic permeability, that is, it has a higher inductance value at the same time.
[0076] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. An integrated inductor, characterized in that: The integrated inductor includes medium crystallization degree magnetic powder and high crystallization degree magnetic powder inside; The medium-crystallization magnetic powder has a crystallinity of 40% to 80%; The high-crystallization magnetic powder has a crystallinity of >95%; The structure of the medium-crystallized magnetic powder is a structure in which an amorphous phase surrounds a nanocrystalline phase.
2. The integrated inductor according to claim 1, characterized in that: The grain size of the medium-crystallized magnetic powder is 10nm-100nm; Preferably, in a two-dimensional plane, the ratio of the number of particles of the high-crystallization magnetic powder to the number of particles of the medium-crystallization magnetic powder is (5-30):1; Preferably, the iron content of the medium-crystallization magnetic powder is 70wt%-95wt%; Preferably, the iron content of the high-crystallization magnetic powder is 45wt%-95wt%.
3. A method for preparing an integrated inductor according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: Mixing low-crystallization magnetic powder, high-crystallization magnetic powder, a coating agent, a binder and a release agent to obtain a mixed powder; integrally forming a coil with the mixed powder, and after annealing, obtaining an integrated inductor; The low-crystallization magnetic powder has a crystallinity of <30%; the integrated inductor includes medium-crystallization magnetic powder and high-crystallization magnetic powder; the medium-crystallization magnetic powder has a crystallinity of 40%-80%; the high-crystallization magnetic powder has a crystallinity of >95%; the medium-crystallization magnetic powder has a structure in which an amorphous phase surrounds a nanocrystalline phase structure.
4. The preparation method according to claim 3, characterized in that: The method for mixing low-crystallization magnetic powder, high-crystallization magnetic powder, coating agent, binder and release agent comprises: The low-crystallization magnetic powder, high-crystallization magnetic powder and coating agent are first mixed, and then a binder is added and mixed, granulated, sieved, and then a release agent is added and mixed.
5. The preparation method according to claim 3 or 4, characterized in that: The iron content of the low-crystallization magnetic powder is 70wt%-95wt%; Preferably, the particle size D50 of the low crystallinity magnetic powder is 5 μm-50 μm; Preferably, based on the total mass of the low-crystallization magnetic powder and the high-crystallization magnetic powder, the content of the low-crystallization magnetic powder is 10wt%-90wt%.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The iron content of the high crystallinity magnetic powder is 45wt%-95wt%; Preferably, the particle size D50 of the high crystallinity magnetic powder is 1 μm-10 μm.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The coating agent includes any one of kaolin, talc or mica powder or a combination of at least two of them; Preferably, based on the total mass of the low-crystallization magnetic powder and the high-crystallization magnetic powder, the added amount of the coating agent is 0.1wt%-3wt%; Preferably, based on the total mass of the low-crystallization magnetic powder and the high-crystallization magnetic powder, the amount of the binder added is 0.5wt%-3wt%; Preferably, the release agent comprises any one of zinc stearate, aluminum stearate or calcium stearate or a combination of at least two thereof; Preferably, based on the total mass of the low-crystallization magnetic powder and the high-crystallization magnetic powder, the added amount of the release agent is 0.5wt%-2wt%.
8. The preparation method according to any one of claims 3 to 7, characterized in that: The integral molding pressure is 500MPa-2000MPa; Preferably, the annealing temperature is 300°C-700°C; Preferably, the annealing time is 0.1h-5h.
9. The preparation method according to claim 3, characterized in that: The preparation method comprises the following steps: First, a low-crystallization magnetic powder with an iron content of 70wt%-95wt%, a particle size D50 of 5μm-50μm, and a crystallinity of less than 30%, a high-crystallization magnetic powder with an iron content of 45wt%-95wt%, a particle size D50 of 1μm-10μm, and a crystallinity of more than 95% and a coating agent are mixed, and then a binder is added to mix, granulate, sieve, and then a release agent is added to mix to obtain a mixed powder; a coil and the mixed powder are integrally formed under a pressure of 500MPa-2000MPa, and after annealing at 300℃-700℃ for 0.1h-5h, an integrated inductor is obtained; The integrated inductor includes medium crystallinity magnetic powder and high crystallinity magnetic powder; the crystallinity of the medium crystallinity magnetic powder is 40%-80%, and the crystallinity of the high crystallinity magnetic powder is >95%; the structure of the medium crystallinity magnetic powder is an amorphous phase surrounding a nanocrystalline phase structure; based on the total mass of the low crystallinity magnetic powder and the high crystallinity magnetic powder, the content of the low crystallinity magnetic powder is 10wt%-90wt%; based on the total mass of the low crystallinity magnetic powder and the high crystallinity magnetic powder, the added amount of the coating agent is 0.1wt%-3wt%, the added amount of the binder is 0.5wt%-3wt%, and the added amount of the release agent is 0.5wt%-2wt%.
10. An application of an integrated inductor, characterized in that: The integrated inductor according to claim 1 or 2, or the integrated inductor prepared by the preparation method according to any one of claims 3 to 9, is applied to a magnetic component.
Citation Information
Patent Citations
Integrated co-fired inductor and preparation method thereof
CN112435844A
Integrated co-fired inductor as well as preparation method and application thereof
CN112735797A
Cited By
Magnetic powder core density and yield optimization design method based on discrete element simulation
CN122452273A